2021
DOI: 10.1111/jvim.16119
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor‐1 concentrations in healthy cats before and after weight gain and weight loss

Abstract: Background: Measurement of serum concentrations of insulin-like growth factor (IGF)-1 is used to diagnose acromegaly in cats.Hypothesis: Changes of body weight do not affect serum concentrations of IGF-1 in cats.Animals: Ten healthy purpose-bred cats.Methods: Prospective study. In lean cats, food availability was stepwise increased during the first week and given ad libitum for a total of 40 weeks to increase their body weight. From week 41 to week 60, food access was limited to reach a weight loss of 1% to 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another factor potentially affecting IGF-1 concentration and impacting the RI might be the body weight of included cats. Although weight gain or weight loss was not associated with significant changes in IGF-1 concentration in a small study including ten healthy research cats [ 37 ], Strage et al detected a significant association between body weight and IGF-1 in 55 healthy cats [ 23 ]. In that previous study, an increase of 1 kg in body weight was associated with an estimated increase in IGF-1 concentration of 38% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor potentially affecting IGF-1 concentration and impacting the RI might be the body weight of included cats. Although weight gain or weight loss was not associated with significant changes in IGF-1 concentration in a small study including ten healthy research cats [ 37 ], Strage et al detected a significant association between body weight and IGF-1 in 55 healthy cats [ 23 ]. In that previous study, an increase of 1 kg in body weight was associated with an estimated increase in IGF-1 concentration of 38% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prospective, experimental study was approved by the Cantonal Veterinary Office, ethics committee, license number ZH118/16, was conducted in accordance with Animal Welfare Act of Switzerland as part of a larger concurrent study (19), and is reported in accordance with ARRIVE guidelines. Cats were acquired as kittens, years before, as research animals from a breeding station for research animals (Liberty Research Inc., Waverly New York 14892, United States).…”
Section: Methodsmentioning
confidence: 99%
“…During the first week of dietary intervention, the daily ration was stepwise increased. In particular, during the first 2 days each cat was fed the resting energy requirement (19) increased by 50%. The daily resting energy requirement was doubled on day 3 and 4.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations